(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
The article continues the study of interoceptive awareness as one of the relevant aspects of improving the psychophysical condition of students. The Multidimensional Assessment of Interoceptive Awareness is a questionnaire used by the world’s leading scientists to study this question. Its latest version, MAIA-2, released in 2018, is most often used. The original questionnaire contains of 8 scales: "Noticing," "Not-Distracting," "Not-Worrying," "Attention Regulation," "Emotional Awareness," "Self-Regulation," "Body Listening," and "Trusting."In the previous article, the data of the "Noticing" scale were published. Research material and methods. 50 first-year students of the Faculty of Health, Physical Education and Sports participated in the survey. The sample was homogeneous in terms of age. All students were 17 years old and consented to the processing of their personal data. The survey was conducted using the Ukrainian version of the Multidimensional Assessment of Interoceptive Awareness (MAIA-2ukr). The purpose of the study is to evaluate the "skills of not being distracted" (domain of interoceptive awareness) of first-year students of the Faculty of Health, Physical Education, and Sports. The results. "Not-Distracting" is an important area of interoceptive awareness. For example, received answers to the question "1. I ignore physical tension or discomfort until it becomes more serious" showed that the lowest score was given by 12% of respondents — "I ignore physical tension or discomfort until they become more severe." Therefore, 12% of first-year students of the Faculty of Health, Physical Education and Sport always ignore "physical tension or discomfort until they become more severe," which is dangerous for physical and mental health. In future publications, we plan to highlight the results of the study of 6 other domains of interoceptive awareness.